Effects of altitude and harvesting dates on morphological characteristics, yield and nutritive value of desho grass (Pennisetum pedicellatum Trin.) in Ethiopia - Asmare, Bimrew; Demeke, Solomon; Tolemariam, Taye; Tegegne, Firew; Haile, Aynalem; Wamatu, Jane (Elsevier, 2017)
Abstract The effects of altitude and harvesting period on the performance of desho grass were evaluated in Ethiopia. A factorial arrangement of treatments was employed with a combination of two altitudes and three harvesting dates. Planting and management of desho grass was undertaken according to recommendations for the species. The data collected consisted of plant height, number of tillers, number and length of leaves, leaf-to-stem ratio and fresh yield. Chemical analysis of the constituents of desho grass samples was completed according to standard procedures. All data were subjected to two analysis of variance procedures and Pearson correlation analysis, with significance tested at p